1967
DOI: 10.1246/bcsj.40.1913
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of Bimolecular Nucleophilic Substitution. IV. Rates of the SN2 and E2 Reactions of β-Substituted Ethyl Chlorides with Sodium Acetate in Aqueous Solutions

Abstract: Rates in the SN2 and E2 reactions of a series of β-substituted ethyl chloride (RCH2CH2Cl, R=Et, MeO, PhO, Gl, and H) in aqueous solutions have been measured at temperatures ranging from 90 to 150°C, using sodium acetate as a nucleophile. The mild rate-retarding effect of β-subtituents in the SN2 reactions, observed in the rate order, H>Et>MeO>Cl>PhO, may be attributed to the steric effects. In a similar fashion, the retardation of E2 reaction rates by the β-substituents, which is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 12 publications
1
21
1
Order By: Relevance
“…This is probably due to the delocalized nature of the charge in the acetate anion. The overall free energy of activation is 21.3 kcal/mol, smaller than the experimental value of 28.2 kcal/mol 24,27,230. at 373 K. Note that solute-solvent charge transfer is not taken into account by the present treatment.…”
Section: Resultscontrasting
confidence: 56%
“…This is probably due to the delocalized nature of the charge in the acetate anion. The overall free energy of activation is 21.3 kcal/mol, smaller than the experimental value of 28.2 kcal/mol 24,27,230. at 373 K. Note that solute-solvent charge transfer is not taken into account by the present treatment.…”
Section: Resultscontrasting
confidence: 56%
“…14 The experimental ∆G ‡ for this reaction in water at 120°C is 29.6 kcal/ mol. 17 The dependence of rate constant on temperature over a narrow (20 degrees) temperature range gives an activation enthalpy ∆H ‡ ) 19.6 kcal/mol and an activation entropy ∆S ‡ ) -26.5 cal M -1 K -1 , from which ∆G ‡ of 27.5 kcal/mol can be obtained at 25°C. As in the case of the formate plus methyl chloride reaction, the calculated ∆G ‡ value is slightly below the extrapolated experimental value.…”
Section: Discussionmentioning
confidence: 99%
“…8 Experimental rate constants for the uncatalyzed S N 2 displacement of chloride by carboxylates have been determined at elevated temperatures. [16][17][18] The rate constants at room temperature can be obtained by extrapolation of known rate constants, 27 estimated from similar reactions, 14 or calculated quantum mechanically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete reaction of both isomers was achieved after about 10 h. As suspected, the C 3 isomer reacted considerably faster than the C 2 isomer. This is probably a steric effect, since for S N 2 reactions, steric effects are generally more important than electronic effects for substituents located at the β position or more remotely 40. A similar analysis performed on the isomeric 2‐ and 3‐PIB‐1‐(3‐bromopropyl)pyrroles showed that for the case of a 3‐carbon tether, the two isomers displayed more nearly the same reactivity.…”
Section: Resultsmentioning
confidence: 92%